2021
DOI: 10.1177/10732748211019138
|View full text |Cite
|
Sign up to set email alerts
|

Role of Autophagy and Apoptosis in Acute Lymphoblastic Leukemia

Abstract: Background: Acute lymphoblastic leukemia (ALL) is a malignant disease characterized by an excessive number of immature lymphocytes, including immature precursors of both B- and T cells. ALL affects children more often than adults. Immature lymphocytes lead to arrested differentiation and proliferation of cells. Its conventional treatments involve medication with dexamethasone, vincristine, and other anticancer drugs. Although the current first-line drugs can achieve effective treatment, they still cannot preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 95 publications
2
11
0
Order By: Relevance
“…Since their discovery in the 1950s, glucocorticoids play an essential role in the treatment of ALL because of their ability to block cell-cycle progression and induce apoptosis in ALL cells. Many publications have reported a positive correlation between in vitro corticoid responses of leukemic lymphoblasts and in vivo responses to glucocorticoid monotherapy [ 11 ]. Among glucocorticoids, prednisolone has been the most commonly used drug in ALL therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Since their discovery in the 1950s, glucocorticoids play an essential role in the treatment of ALL because of their ability to block cell-cycle progression and induce apoptosis in ALL cells. Many publications have reported a positive correlation between in vitro corticoid responses of leukemic lymphoblasts and in vivo responses to glucocorticoid monotherapy [ 11 ]. Among glucocorticoids, prednisolone has been the most commonly used drug in ALL therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the DEPs enriched in each pathway are shown in Supplementary Tables S5 – 7 . The results showed that all DEPs were significantly enriched in the Notch and autophagy pathways, which have been previously associated with the occurrence and development of ALL 16 , 17 .
Figure 4 Gene ontology function enrichment analysis of the differentially expressed proteins (DEPs).
…”
Section: Resultsmentioning
confidence: 61%
“…Additionally, Takam et al described a modulatory effect of the Notch pathway in B-ALL, with Notch pathway suppression leading to increased chemosensitivity of B-ALL cells 27 . Autophagy was also previously associated with the development of ALL 17 . Collectively, these findings suggest that the Notch signaling and autophagy pathways contribute to the progression of B-ALL.…”
Section: Discussionmentioning
confidence: 84%
“…Recent studies suggest that inhibiting autophagy may be an efficient approach to improve the chemotherapeutic antileukemic regimens. Through suppressing autophagy in ETV6-RXNX1 gene positive B-ALL could severely downregulate cell proliferation and survival [52]. For example, an autophagy inhibitor, choloroquine, could increase the response of patients with B-ALL to the chemotherapy [53].…”
Section: Ocs and Leukemiamentioning
confidence: 99%
“…Furthermore, hydroxychloroquine, an autophagy inhibitor, reduces proliferation and survival of leukemic blasts in ALL [54]. Targeting suppressing autophagy in T-ALL was also effective and could be used to support further clinical trials in the future [52]. However, how secretory lysosomes in osteoclasts work still needs to be clarified.…”
Section: Ocs and Leukemiamentioning
confidence: 99%